Nutritional, microbiological, and feasibility evaluation of sorghum-based hummus - Pike, Madeleine (My University, 2026)
Sorghum is a drought-resistant cereal crop cultivated worldwide; however, it remains underutilized in human food applications. Hummus represents a familiar product format for incorporating alternative grains, offering an opportunity to enhance food security while developing sorghum-based foods with improved nutritional properties. Despite this potential, limited information is available on the nutritional performance, microbiological stability, and feasibility of sorghum-based hummus. Therefore, the objective of this study was to evaluate the nutritional quality, microbiological stability, and sensory acceptance of sorghum-based hummus formulations compared to traditional chickpea hummus. Hummus formulations were prepared using chickpea, red sorghum, and white sorghum. To evaluate microbial shelf-life stability, a thymol-based emulsion was incorporated into selected formulations, and products were experimentally inoculated with Listeria monocytogenes, Staphylococcus aureus, and Salmonella spp. Microbial populations were monitored during refrigerated storage for 7 days. In vitro protein digestibility was assessed to compare the nutritional performance of the formulations, and sensory acceptance was evaluated through consumer testing. Data were analyzed using mixed-effects models and confidence interval estimation (α = 0.05). No significant differences were observed between thymol-treated and untreated samples across grain types (p > 0.05); therefore, microbiological analyses were restricted to day 7, confirming the product's stability under the evaluated conditions. Red and white sorghum hummus exhibited significantly higher protein digestibility than traditional chickpea hummus, with increases ranging from 4% to 7% (p < 0.05). Sensory evaluation indicated that chickpea hummus was preferred overall; however, consumers expressed a willingness to consider sorghum-based hummus when it was associated with added health benefits. Sorghum-based hummus represents a promising alternative to conventional formulations, aligning nutritional benefits with food security goals. Our research demonstrated that sorghum could provide improved protein digestibility and maintain microbiological stability, supporting its feasibility as a value-added food product.
Keywords: Sorghum, Microbiological, Nutritional, Feasibility